Evaluation of Internal Control Activities Operating Income On Technical Implementation Unit (UPTD) Terminal Joyoboyo Surabaya - Yanna Eka Pratiwi; Supartini Supartini (LPPM of NAROTAMA UNIVERSITY, 2018)
This study aims to determine whether the application of internal control activities on operating income has been running effectively. This research method using quantitative analysis of the factors which is causing a problem, for that we need the internal control over operating income, and using qualitative data analysis techniques in order to determine as to whether the evaluation of internal control penapatan reception operations have been implemented effectively. The results of this study indicate that the implementation of the internal control on the Terminal UPTD Joyoboyo can not be implemented, the implementation of internal control can only be done if the amendment to the accounting system as well as the separation of the functions necessary to anticipate the implications fungsi.Sebagai geminating expected by the authors is the need to change the system accounting is centralized to decentralized, monitoring needs to be optimized, it is expected the separation of the functions to avoid geminating functions.